Effective probiotic regimens for bacterial vaginosis treatment and recurrence prevention: A systematic review - Udjianto, Udjianto; Sirat, Noorhamdani A.; Rahardjo, Bambang; Zuhriyah, Lilik (Narra J, 2025)
Probiotics represent a promising alternative therapy for bacterial vaginosis; however, consensus on the most effective species, strains, and doses remains lacking, and long-term safety data are limited. The aim of this study was to evaluate the effectiveness of probiotics in managing bacterial vaginosis, considering species, strain, clinical outcomes, optimal dosage, duration, and side effects. This study included randomized-controlled trials (RCTs) published in English (2014–2024) on probiotic treatment for bacterial vaginosis, assessing species, strain, dose, duration, and efficacy. A systematic search was conducted on December 20, 2024, in Scopus, Web of Science, and PubMed using the keywords "vaginosis," "bacterial vaginosis," and "probiotic." Data were extracted and synthesized, and study quality was assessed using the Risk of Bias 2 tool, while NVivo 14 software facilitated thematic analysis. The systematic search yielded 1,560 initial records, of which 16 RCTs were included. The findings revealed that Lactobacillus rhamnosus TOM 22.8 (10×10⁹ CFU/day for 10 days) was the most effective strain and dose, significantly improving Nugent scores, vaginal pH, and microbiota composition and reducing bacterial vaginosis recurrence rate. Alternative strains, including L. crispatus, L. plantarum, and L. acidophilus, showed therapeutic potential at doses of 1×10⁸ to 5.4×10⁹ CFU/day for treatment durations ranging from 6 days to 4 months. The reported side effects were mild and self-limiting. This study supports the use of probiotics as an adjunctive or alternative bacterial vaginosis treatment, emphasizing the need for a personalized approach based on patient characteristics. However, limitations such as small sample sizes and heterogeneous outcome measures necessitate further research. Larger, well-designed trials with standardized methodologies are required to refine probiotic recommendations.